Additions to the revision of Digonocryptus Viereck (Hymenoptera, Ichneumonidae, Cryptinae), with nine new taxa, new males, and distribution maps for all known species - Aguiar, Alexandre P.; Santos, Bernardo F. (Zootaxa, 2012)
Complementary revisionary information is provided to Digonocryptus Viereck. The males of D. inermis (Szépligeti) andD. sautatus Aguiar et Ramos are described for the first time, and nine species are described as new: D. arlequim Santoset Aguiar, sp. nov., D. hesperus Aguiar et Santos, sp. nov., D. insularis Aguiar et Santos, sp. nov., D. noxignis Aguiar etSantos, sp. nov., D. pontagus Aguiar et Ramos, sp. nov., D. zatheos Santos et Aguiar, sp. nov., and D. zopheros Santos etAguiar, sp. nov.; because of the lack of a statement about the types’ depositories, two of the new names proposed by Agu-iar and Ramos (2011) were unavailable, and the respective species are here described as new taxa, with indication of thetype depositories: D. archisius Aguiar et Ramos, sp. nov., and D. iageus Aguiar et Ramos, sp. nov. The original authorshipis maintained, but the names are valid from the date of publication of this paper. New specimens and new distribution dataare reported for D. arcaeus Aguiar et Ramos, D. atrozyrix Aguiar et Ramos, D. caceres Aguiar et Ramos, D. cennitus Agu-iar et Ramos, D. chiriquensis (Cameron), D. coloratus (Szépligeti), D. crassipes (Brullé), D. denticulatus (Taschenberg),D. diversicolor (Viereck), D. domius Aguiar et Ramos, D. elegans Aguiar et Ramos, D. grossipes (Brullé), D. inermis(Szépligeti), D. inflatus (Brullé), D. mettus Aguiar et Ramos, D. propodeator Kasparyan et Ruíz, D. pulchripes (Camer-on), D. rufigaster (Szépligeti), D. sautatus Aguiar et Ramos, D. silopoeus Aguiar et Ramos, D. sipius Aguiar et Ramos,D. sutor (Fabricius), D. tarsatus (Cresson), D. teleborus Aguiar et Ramos, D. thoracicus Kasparyan et Ruíz, D. variabilisAguiar et Ramos, D. variegatus (Szépligeti), D. varipes (Brullé), and D. yunus Aguiar et Ramos. Illustrations of habitusand diagnostic features are provided for all new taxa and for seven other species, including new images for the males ofsix species, all of them illustrated for the first time. A total of 40 new distribution records are registered for 21 species, and distribution maps are provided for all 52 valid species of the genus.